Business communication for enagic network marketing during the covid-19 pandemic business players : study of business communication on enagic kangen water business actors in the city of Baubau - Asmanang, La Ode (Universitas Ahmad Dahlan, 2022)
Enagic Network marketing business actors in their business communication activities depend on the intensity of interaction with many people to build a business and achieve planned goals. But how is the productivity of business people in business communication? Network marketing is enagic during the Covid-19 pandemic. The use of information technology in the form of applications on Android smartphones such as the WhatsApp application, Facebook social media and communication media zoom cloud meetings are useful tools for Network Marketing businesses to remain productive